Karakteristik Pohon Peneduh Pada Koridor Jalan Perkotaan Di Kota Gorontalo - Saptan Gobel; Sri Maryati; M. Iqbal Liayong Pratama (Universitas Negeri Gorontalo, 2026)
Shade trees are an important element of roadside green corridors that contribute to improving urban environmental quality. This study aims to identify and analyze the characteristics of shade trees along arterial and collector roads in Gorontalo City. A quantitative descriptive method was applied using a spatial analysis approach based on Geographic Information Systems. Data were collected through field observation, vegetation inventory, GPS-based coordinate recording, tree characteristic measurements, and documentation. The results show that there were 1,140 shade trees consisting of 15 species. Mahogany was the dominant species, with 333 trees or 29.21%. Tree characteristics were dominated by medium height of 5–10 m at 60.44%, crown width of 2.5–5.0 m at 57.81%, and trunk diameter of 50–100 cm at 50.88%. The general physical condition of the trees was mostly good, particularly trunk condition at 99.56%, leaf condition at 95.88%, branching condition at 91.58%, and root condition at 69.56%. These findings indicate that shade trees in Gorontalo City support ecological functions, aesthetic quality, and urban environmental comfort.